Method for synthesizing lithium garnet type solid electrolyte
The precursor powder of lithium garnet-type solid electrolyte is prepared by co-precipitation method, and a high-density core and cladding layer is formed through multi-step ball milling and calcining, which solves the problem of difficult to achieve high ionic conductivity, uniform particle size and high density in the prior art, and achieves the improvement of high performance and economic value.
Patent Information
- Application Number
- CN202411780208.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
It is difficult for existing lithium garnet solid electrolytes to achieve high ionic conductivity, uniform particle size and high density during the synthesis process, and the use of sintering agents will reduce the ionic conductivity and purity of the material and increase costs.
The La2Zr2O7 precursor powder was prepared by co-precipitation method, and a high-density lithium garnet-type solid electrolyte was formed through a multi-step ball milling and calcining process of core material and cladding intermediate.
It realizes solid electrolytes with high ionic conductivity, uniform particle size and high density, simplifies the process flow, reduces sintering temperature and equipment losses, and improves the electrochemical performance and economic value of the material.
Smart Images

Figure CN119581650A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a method for synthesizing a lithium garnet type solid electrolyte. Background Art
[0002] At present, people's demand for lithium-ion batteries is growing, but it also exposes problems such as leakage and volatilization of liquid electrolytes or the diaphragm being easily pierced by lithium dendrites, causing short circuits. 12 As one of the solid electrolytes for lithium-ion batteries, it has high ionic conductivity and has great advantages in energy density, thermodynamic and electrochemical stability, and safety. 12 Garnet solid electrolyte has two crystal forms: tetragonal phase and cubic phase. The ionic conductivity of the tetragonal phase is two orders of magnitude lower than that of the cubic phase. At the same time, the ionic conductivity of the high-density electrolyte sheet is higher. 12 In the process of sintering, trace metal elements are usually introduced for element doping to promote cubic phase formation and sintering densification, and sintering aids that can promote densification are added, or more effective tableting equipment is used, or both methods are used at the same time to improve the density of the electrolyte sheet. However, the ionic conductivity of the sintering aid is often low, which will reduce the ionic conductivity of the material, and the residual sintering aid after sintering will also affect the purity of the material. High-performance tableting equipment also increases certain costs.
[0003] Therefore, it is very necessary to research and develop a method for preparing electrolytes with high ionic conductivity, uniform particle size and high density. Summary of the invention
[0004] The present invention aims to solve the above technical problems and provides a method for synthesizing a lithium garnet-type solid electrolyte, which can prepare an electrolyte with high ion conductivity, uniform particle size and high density.
[0005] The technical solution of the present invention is:
[0006] A method for synthesizing a lithium garnet-type solid electrolyte comprises the following steps
[0007] S1. Preparing precursor powder by coprecipitation method: heating and stirring the metal ion solution, adding alkaline solution to adjust the pH value of the solution to 9-12, keeping the pH value stable, aging the solution, filtering to obtain precursor residue, and drying the residue to obtain precursor powder;
[0008] S2. Preparation of core material: lithium source, lanthanum source, precursor powder and doped metal oxide are taken as core raw materials according to the chemical composition ratio, the raw materials are mixed and ball milled, the ball milled material is dried and calcined to obtain core material powder;
[0009] S3. Preparation of coating layer intermediate: taking lanthanum source, precursor powder and doped metal oxide as coating layer intermediate raw materials according to the chemical composition ratio, ball milling each raw material, drying and calcining the ball milled material to obtain coating layer intermediate powder;
[0010] S4, tableting: taking core material powder, coating layer intermediate powder and lithium oxide, mixing and ball milling, drying the ball milled material, sieving the ball milled material, and tableting the sieved powder to obtain a formed sheet;
[0011] S5. Sintering of the formed sheet: Covering the formed sheet with the core material powder and then sintering it, taking out the sheet and grinding and polishing it to obtain a lithium garnet type solid electrolyte.
[0012] Preferably, in S1 of the present invention, the method for preparing the metal ion solution is: weighing and mixing a lanthanum source and a zirconium source in a weight ratio of 1:1, adding them to an acidic solution or deionized water to dissolve the lanthanum source and the zirconium source, and obtaining a metal ion solution with a metal ion concentration of 100-200 g / L.
[0013] Preferably, the acid concentration of the acidic solution of the present invention is 0.1-1.5 mol / L, and the alkali concentration of the alkaline solution is 2-6 mol / L; the acid in the acidic solution is one or more of sulfuric acid, nitric acid, and hydrochloric acid; the alkali in the alkaline solution is one or more of ammonia water, ammonium carbonate, and ammonium bicarbonate.
[0014] Preferably, the lanthanum source of the present invention is one or more of lanthanum oxide, lanthanum carbonate, lanthanum hydroxide and lanthanum nitrate; the zirconium source is one or more of zirconium oxide, zirconium carbonate, zirconium hydroxide and zirconium nitrate.
[0015] Preferably, in S1 of the present invention, the heating temperature of the metal ion solution is 50-70° C., and the stirring speed is 300-600 rpm / min.
[0016] Preferably, in S1 of the present invention, the solution aging time is 10-40 hours, and the precursor residue obtained after filtering the aged solution has a chemical composition of La2Zr2(OH) 14 Or one or both of La2Zr2(CO3).
[0017] Preferably, in S2 of the present invention, the chemical composition of the core material powder is Li 7-nα-β M α LqCy 2-x M' x O 12, wherein 0<α<1, 0≤x≤1, β=(n'-4)x, n is the valence state of element M, n' is the valence state of element M', M is at least one of B, Ca, Al, Y, Sc, Fe, and Ga, and M' is at least one of Ti, Mn, Bi, Sn, Ge, Mo, W, Sb, Nb, and Ta; and the metal doped with the metal oxide is one or more of metal M or M'.
[0018] Preferably, in S3 of the present invention, the chemical composition of the coating intermediate powder is La3Zr 2-x K x O 12 , wherein 0≤x≤1, K is one or more of Ti, Mn, Bi, Sn, Ge, Mo, W, Sb, Nb, and Ta; and the lanthanum source is lanthanum oxide.
[0019] Preferably, in S4 of the present invention, the molar mass ratio of the core material powder, the coating layer intermediate powder and the lithium oxide is 1:0.2:(0.7-1.1).
[0020] Preferably, in S4 of the present invention, the tableting pressure is 30-100 MPa.
[0021] Preferably, in S2 of the present invention, the calcination is carried out in an atmosphere with an oxygen content of 22%-99% and a temperature of 800℃-950℃ for 5-10h; in S3, the calcination is carried out in an atmosphere with an oxygen content of 22%-99% and a temperature of 700℃-850℃ for 5-10h; in S5, the sintering is carried out in an atmosphere with an oxygen content of 22%-99% and a temperature of 1100℃-1200℃ for 5-15h.
[0022] In the method of the present invention, a La2Zr2O7 precursor powder in which La and Zr elements are fully and evenly mixed is prepared by a coprecipitation method, a lithium source, La2O3, a La2Zr2O7 precursor and an oxide doped with metal M or M' are evenly mixed, and the mixture is calcined to obtain a coated core material powder Li 7-nα-β M α LqCy 2-x M' x O 12 ; La2O3, La2Zr2O7 precursors and oxides doped with metal K or K' are mixed evenly, and the mixture is calcined to obtain an intermediate of the coating material, the main phase of the intermediate is La2Zr2O7, and the remaining phase is La2O3 and oxides doped with metal K or K'; finally, LiO, the intermediate of the coating material and the core material powder Li 7-nα-β M α LqCy 2-x M' x O 12After mixing evenly and pressing into tablets, sintering is performed to obtain a coating layer of La3Zr 2- x K x O 12 , the core is Li 7-nα-β M α LqCy 2-x M' x O 12 The solid electrolyte sheet has a high ionic conductivity coating layer that fills the gaps between the crystal particles of the core material, making the solid electrolyte sheet have higher ionic conductivity and density.
[0023] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0024] 1. The solid electrolyte prepared by the method of the present invention has high ion conductivity, uniform particle size and high density.
[0025] 2. The method of the present invention has a simple process. The particle size of the precursor powder can be controlled by the co-precipitation method, and the obtained precursor powder has a uniform particle size distribution and a uniform particle size. The powder in which the La element and the Zr element are fully mixed at the microscopic level can reduce the difficulty of ball milling of the ball milling mixture, and also reduce the temperature of subsequent sintering, which is energy-saving and environmentally friendly, reduces the high-temperature loss of the equipment, and can extend the service life of the equipment.
[0026] 3. In the method of the present invention, the core material powder and coating intermediate powder formed by calcining the precursor powder have the advantages of uniform element distribution, stable morphology and structure, and uniform particle size, which is conducive to the formation of high-purity and high-performance coating layers and cores, improves the electrochemical properties and density of the solid electrolyte, and has high economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope microstructure diagram of the precursor powder of Example 1 of the present invention.
[0028] Figure 2 This is a scanning electron microscope microstructure image of the cross section of the electrolyte sheet of Example 4 of the present invention. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] S1. Preparing precursor powder by co-precipitation method: lanthanum oxide and zirconium oxide are weighed and mixed in a weight ratio of 1:1, dissolved in 0.1 mol / L sulfuric acid solution to prepare a metal ion solution with an ion concentration of 100 g / L, and 4 mol / L NH4HCO3 alkaline solution is prepared as a precipitant; under the conditions of a reaction temperature of 50°C and a stirring speed of 500 rpm / min, the precipitant solution is continuously added dropwise to the metal ion solution to maintain the solution pH value at 10-10.5, and after the pH value stabilizes, the solution is aged for 20 hours, and the solution is filtered to obtain La2Zr2O7 precursor residue, and the La2Zr2O7 precursor residue is dried at a constant temperature of 80°C to constant weight to obtain La2Zr2O7 precursor powder, and its scanning electron microscope microstructure is shown in Figure 1 ,like Figure 1 As shown, the obtained precursor powder has uniform particle size distribution and an irregular spherical shape;
[0032] S2. Preparation of core material: According to the core material Li 6.6 Al 0.2 B 0.2 La3Zr2O 12 The stoichiometric ratio of Li:Al:B:La:Zr is 6.6:0.2:0.2:3:2. Lithium carbonate, lanthanum oxide, La2Zr2O7 precursor powder, aluminum oxide and boron oxide are weighed as the core raw materials, wherein the mass of lithium carbonate exceeds the theoretical value by 3%. The core raw materials are put into a planetary ball mill. Small zirconium oxide balls (diameter 2mm), medium balls (diameter 4mm) and large balls (diameter 8mm) are mixed into mixed zirconium balls in a mass ratio of 3:2:1 and put into the planetary ball mill. The ball-material mass ratio is 1.5:1. Anhydrous ethanol is added as a ball milling agent at a liquid-solid ratio of 2:1. The mixture is ball milled at 270r / min for 6h. After the ball milling, it is placed in a vacuum drying oven and dried at 80℃ for 8h. After the drying, it is calcined at 950℃ for 5h in an air atmosphere, and then cooled to room temperature at 4℃ / min to obtain Li 6.6 Al 0.2 B 0.2 La3Zr2O 12 Core material powder;
[0033] S3. Preparation of coating layer intermediate powder: according to the coating material La3Zr 1.6 Mo 0.2 Ta 0.2 O 10The stoichiometric ratio of La:Zr:Mo:Ta=3:1.6:0.2:0.2 is used to weigh lanthanum oxide, La2Zr2O7 precursor powder, molybdenum oxide and tantalum oxide as coating layer intermediate raw materials; the coating layer intermediate raw materials are placed in a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2; after the ball milling, the raw materials are placed in a vacuum drying oven at 80°C for 8h, and after the drying, the temperature is increased to 850°C at a heating rate of 3°C / min in an air atmosphere, and the temperature is kept for calcination for 5h, and then the temperature is reduced to room temperature at 4°C / min to obtain a coating layer intermediate powder;
[0034] S4, tableting: first press the core material powder Li 6.6 Al 0.2 B 0.2 La3Zr2O 12 :Coating layer intermediate powder La3Zr 1.6 Mo 0.2 Ta 0.2 O 10 : lithium oxide = 1:0.2:0.7 molar mass ratio is put into a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2. After the ball milling is completed, it is placed in a vacuum drying oven at 80°C for 8 hours. After the ball milling material is dried, it is passed through a 200-mesh sieve, and the sieved powder is pressed at 30 MPa to obtain a formed sheet;
[0035] S5. Sintering of the formed sheet: Cover the formed sheet with the core material powder and then sinter it, the mass ratio of the core material powder to the formed sheet is 1:5, to obtain a powder-buried sheet; heat the buried sheet to 1150°C at a heating rate of 3°C / min in an air atmosphere, and sinter it for 15 hours, then cool it to room temperature at a rate of 4°C / min, take out the sintered sheet, and grind and polish it to obtain a lithium garnet-type solid electrolyte sheet 1.
[0036] Example 2
[0037] S1. Preparing precursor powder by co-precipitation method: weigh lanthanum carbonate and zirconium carbonate according to the stoichiometric ratio, dissolve them in 1.5 mol / L nitric acid solution to prepare a metal ion solution with an ion concentration of 150 g / L, and prepare 2 mol / L (NH4)2CO3 alkaline solution as a precipitant; under the conditions of reaction temperature of 65°C and stirring speed of 500 rpm / min, continuously add precipitant solution to the metal ion solution to maintain the pH value of the solution at 10-10.5, age the solution for 20 hours after the pH value stabilizes, filter the solution to obtain La2Zr2O7 precursor residue, and dry the La2Zr2O7 precursor residue at 80°C to constant weight to obtain La2Zr2O7 precursor powder;
[0038] S2. Preparation of core material powder: According to the core material Li 6.6 Ca 0.2 Y0.2 LqCy 1.6 Ta 0.4 O 12 The stoichiometric ratio of Li:Ca:Y:La:Zr:Ta is 6.6:0.2:0.2:3:1.6:0.4. Lithium carbonate, lanthanum oxide, La2Zr2O7 precursor powder, calcium oxide, yttrium oxide and tantalum oxide are weighed as core raw materials, wherein the mass of lithium carbonate exceeds the theoretical value by 3wt%. The core raw materials are put into a planetary ball mill, and small zirconium oxide balls (diameter 2mm), medium balls (diameter 4mm) and large balls (diameter 8mm) are mixed into mixed zirconium balls in a mass ratio of 3:2:1 and put into a planetary ball mill, and the ball-material mass ratio is 1.5:1. Anhydrous ethanol is added as a ball milling agent at a liquid-solid ratio of 2:1, and the mixture is ball-milled at 270r / min for 6h; after the ball milling, it is placed in a vacuum drying oven and dried at 80℃ for 8h. After the drying, it is calcined at 850℃ for 8h in an air atmosphere, and then cooled to room temperature at 4℃ / min to obtain Li 6.6 Ca 0.2 Y 0.2 LqCy 1.6 Ta 0.4 O 12 Core material powder;
[0039] S3. Preparation of coating layer intermediate powder: according to the coating material La3Zr 1.6 Ti 0.2 Mn 0.2 O 10 Lanthanum oxide, La2Zr2O7 precursor powder, titanium dioxide and manganese oxide are weighed as coating layer intermediate raw materials in a stoichiometric ratio of La:Zr:Ti:Mn=3:1.6:0.2:0.2; the coating layer intermediate raw materials are placed in a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2; after the ball milling, the raw materials are placed in a vacuum drying oven at 80°C for 8h, and after the drying, the temperature is increased to 700°C at a heating rate of 3°C / min in an air atmosphere, and the temperature is kept for calcination for 10h, and then the temperature is reduced to room temperature at 4°C / min to obtain a coating layer intermediate powder;
[0040] S4, tableting: first press the core material powder Li 6.6 Ca 0.2 Y 0.2 LqCy 1.6 Ta 0.4 O 12 :Coating layer intermediate powder La3Zr 1.6 Ti 0.2 Mn 0.2 O 10: lithium oxide = 1:0.2:1.1 molar mass ratio is put into a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2. After the ball milling is completed, it is placed in a vacuum drying oven at 80° C. for 8 hours. After the ball milling material is dried, it is passed through a 200-mesh sieve, and the sieved powder is pressed at 30 MPa to obtain a formed sheet;
[0041] S5. Sintering of the formed sheet: Cover the formed sheet with the core material powder and then sinter it, the mass ratio of the core material powder to the formed sheet is 1:5, to obtain a powder-buried sheet; heat the buried sheet to 1100°C at a heating rate of 3°C / min in an air atmosphere, sinter it for 15 hours, then cool it to room temperature at a rate of 4°C / min, take out the sintered sheet, grind and polish it, and obtain a lithium garnet-type solid electrolyte sheet 2.
[0042] Example 3
[0043] S1. Preparing precursor powder by co-precipitation method: weigh lanthanum hydroxide and zirconium hydroxide according to the stoichiometric ratio, dissolve them in 1.0 mol / L hydrochloric acid solution to prepare a metal ion solution with an ion concentration of 200 g / L, and prepare 6 mol / L NH3H2O alkaline solution as a precipitant; under the conditions of reaction temperature of 60°C and stirring speed of 500 rpm / min, continuously add precipitant solution to the metal ion solution to maintain the pH value of the solution at 11.5-12, age the solution for 20 hours after the pH value stabilizes, filter the solution to obtain La2Zr2O7 precursor residue, and dry the La2Zr2O7 precursor residue at 80°C to constant weight to obtain La2Zr2O7 precursor powder;
[0044] S2. Preparation of core material: According to the core material Li 6.6 Sc 04 LqCy 1.6 Ti 0.1 Mn 0.1 W 0.1 Nb 0.1 O 12The stoichiometric ratio of Li:Sc:La:Zr:Ti:Mn:W:Nb is 6.6:0.4:3:1.6:0.1:0.1:0.1:0.1. Lithium carbonate, lanthanum oxide, La2Zr2O7 precursor powder, cerium oxide, titanium dioxide, manganese oxide, tungsten oxide and niobium oxide are weighed as core raw materials, wherein the mass of lithium carbonate is 3% in excess. The core raw materials are put into a planetary ball mill, and zirconium oxide small balls (diameter 2 mm), medium balls (diameter 4mm) and large balls (diameter 8mm) are mixed into a mixed zirconium ball in a mass ratio of 3:2:1 and put into a planetary ball mill with a ball-to-material mass ratio of 1.5:1. Anhydrous ethanol is added as a ball milling agent at a liquid-to-solid ratio of 2:1, and the mixture is ball milled at 270r / min for 6h; after the ball milling, the mixture is placed in a vacuum drying oven at 80℃ for 8h, and after the drying, it is calcined at 800℃ for 10h in an oxygen atmosphere (oxygen content = 99%), and then cooled to room temperature at 4℃ / min to obtain Li 6.6 Sc 04 LqCy 1.6 Ti 0.1 Mn 0.1 W 0.1 Nb 0.1 O 12 Core material powder;
[0045] S3. Preparation of coating layer intermediate powder: according to the coating material La3Zr 1.6 Sn 0.2 Bi 0.2 O 10 Lanthanum oxide, La2Zr2O7 precursor powder, tin oxide and bismuth oxide are weighed as coating layer intermediate raw materials in a stoichiometric ratio of La:Zr:Sn:Bi=3:1.6:0.2:0.2; the coating layer intermediate raw materials are placed in a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2; after the ball milling, the raw materials are placed in a vacuum drying oven at 80°C for 8h, and after the drying, the temperature is increased to 850°C at a heating rate of 3°C / min in an air atmosphere, and the temperature is kept for calcination for 6h, and then the temperature is reduced to room temperature at 4°C / min to obtain a coating layer intermediate powder;
[0046] S4, tableting: first press the core material powder Li 6.6 Sc 04 LqCy 1.6 Ti 0.1 Mn 0.1 W 0.1 Nb 0.1 O 12 :Coating layer intermediate powder La3Zr 1.6 Sn 0.2 Bi 0.2 O 10: lithium oxide = 1:0.2:1.0 molar mass ratio is put into a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2. After the ball milling is completed, it is placed in a vacuum drying oven at 80° C. and dried for 8 h. After the ball milling material is dried, it is passed through a 200-mesh sieve, and the sieved powder is pressed at 30 MPa to obtain a formed sheet;
[0047] S5. Sintering of the formed sheet: Cover the formed sheet with the core material powder and then sinter it, the mass ratio of the core material powder to the formed sheet is 1:5, to obtain a powder-buried sheet; heat the buried sheet to 1200°C at a heating rate of 3°C / min in an air atmosphere, sinter it for 8 hours, then cool it to room temperature at a rate of 4°C / min, take out the sintered sheet, grind and polish it, and obtain a lithium garnet-type solid electrolyte sheet 3.
[0048] Example 4
[0049] S1. Preparing precursor powder by co-precipitation method: weigh lanthanum nitrate and zirconium nitrate according to the stoichiometric ratio, dissolve them in 1.0 mol / L hydrochloric acid solution to prepare a metal ion solution with an ion concentration of 200 g / L, and prepare 6 mol / L NH3H2O alkaline solution as a precipitant; under the conditions of reaction temperature of 70°C and stirring speed of 500 rpm / min, continuously add precipitant solution to the metal ion solution to maintain the pH value of the solution at 9-9.5, age the solution for 20 hours after the pH value stabilizes, filter the solution to obtain La2Zr2O7 precursor residue, and dry the La2Zr2O7 precursor residue at 80°C to constant weight to obtain La2Zr2O7 precursor powder;
[0050] S2. Preparation of core material: According to the core material Li 6.6 Ga 0.4 LqCy 1.6 Bi 0.1 Sn 0.1 W 0.2 O 12 The stoichiometric ratio of Li:Ga:La:Zr:Bi:Sn:W is 6.6:0.4:3:1.6:01:0.1:0.2. Lithium carbonate, lanthanum oxide, La2Zr2O7 precursor powder and gallium oxide, tin oxide, tungsten oxide and bismuth oxide are weighed as core raw materials, wherein the lithium carbonate mass is 3% in excess. The core raw materials are put into a planetary ball mill. Small zirconium oxide balls (diameter 2mm), medium balls (diameter 4mm) and large balls (diameter 8mm) are mixed into mixed zirconium balls in a mass ratio of 3:2:1 and put into the planetary ball mill. The ball-to-material mass ratio is 1.5:1. Anhydrous ethanol is added as a ball milling agent at a liquid-to-solid ratio of 2:1. The mixture is ball-milled at 270r / min for 6h. After the ball milling, it is placed in a vacuum drying oven and dried at 80℃ for 8h. After the drying, it is calcined at 850℃ for 8h in an air atmosphere, and then cooled to room temperature at 4℃ / min to obtain Li 6.6Ga 0.4 LqCy 1.6 Bi 0.1 Sn 0. 1W 0.2 O 12 Core material powder;
[0051] S3. Preparation of coating layer intermediate powder: according to the coating material La3Zr 1.6 W 0.2 Nb 0.2 O 10 Lanthanum oxide, La2Zr2O7 precursor powder, tungsten oxide and niobium oxide are weighed as coating layer intermediate raw materials with a stoichiometric ratio of La:Zr:W:Nb=3:1.6:0.2:0.2; the coating layer intermediate raw materials are placed in a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2; after the ball milling, the raw materials are placed in a vacuum drying oven at 80°C for 8h, and after the drying, the temperature is increased to 750°C at a heating rate of 3°C / min in an air atmosphere, and the temperature is kept for calcination for 8h, and then the temperature is reduced to room temperature at 4°C / min to obtain a coating layer intermediate powder;
[0052] S4, tableting: first press the core material powder Li 6.6 Ga 0.4 LqCy 1.6 Bi 0.1 Sn 0.1 W 0.2 O 12 :Coating layer intermediate powder La3Zr 1.6 W 0.2 Nb 0.2 O 10 : lithium oxide = 1:0.2:0.9 molar mass ratio is put into a planetary ball mill, and the ball milling process is the same as the ball milling process in step S2. After the ball milling is completed, it is placed in a vacuum drying oven at 80° C. for 8 hours. After the ball milling material is dried, it is passed through a 200-mesh sieve. The sieved powder is pressed at 30 MPa to obtain a formed sheet;
[0053] S5. Sintering of the formed sheet: The formed sheet is covered with the core material powder and then sintered, the mass ratio of the core material powder to the formed sheet is 1:5, to obtain a powder-embedded sheet; the powder-embedded sheet is heated to 1200°C at a heating rate of 3°C / min in an air atmosphere, and then sintered for 15 hours, and then cooled to room temperature at a rate of 4°C / min. The sintered sheet is taken out and polished to obtain a lithium garnet-type solid electrolyte sheet 4, the scanning electron microscope microstructure of which cross section is shown in the following figure: Figure 2 As shown, from Figure 2 As shown, the particles in the cross section of the electrolyte sheet are in close contact with each other, and the expansion of the high-density contact area can effectively improve the lithium ion transmission efficiency of the material and improve the ion conductivity.
[0054] Example 5
[0055] The difference from Example 3 is that the core material in step 2 is Li 6.6 Fe 0.4 LqCy 1.6 Ge 0.2 Mo 0.2 O 12 (Weigh lithium carbonate, lanthanum oxide, La2Zr2O7 precursor powder and iron oxide, germanium dioxide, and molybdenum oxide as core raw materials, wherein the lithium carbonate mass excess is 3%); the coating layer intermediate material in step 3 is La3Zr 1.8 Sb 0.2 O 10 (Weigh lanthanum oxide, La2Zr2O7 precursor powder and antimony oxide as coating layer intermediate raw materials), the rest is the same as Example 3, and finally a lithium garnet type solid electrolyte sheet 5 is obtained.
[0056] Example 6
[0057] The difference from Example 3 is that the core material in step 2 is Li 6.6 Al 0.4 LqCy 1.6 Sb 0.2 W 0.2 O 12 (Weigh lithium carbonate, lanthanum oxide, La2Zr2O7 precursor powder and aluminum oxide, antimony oxide, tungsten oxide as core raw materials, among which lithium carbonate has a 3% excess mass); the coating layer intermediate material in step 3 is Li7La3Zr 1.6 Ge 0.2 Sb 0.2 O 10 (Weigh lanthanum oxide, La2Zr2O7 precursor powder, germanium dioxide and antimony oxide as coating layer intermediate raw materials), the rest is the same as Example 3, and finally a lithium garnet type solid electrolyte sheet 6 is obtained.
[0058] Comparative Example 1
[0059] The difference from Example 4 is that the molar mass ratio of core material powder: coating layer intermediate powder: lithium oxide is 1:0.2:0.5, and the rest is the same as Example 4.
[0060] Comparative Example 2
[0061] The difference from Example 4 is that the molar mass ratio of core material powder: coating layer intermediate powder: lithium oxide is 1:0.2:1.3, and the rest is the same as Example 4.
[0062] Comparative Example 3
[0063] The difference from Example 4 is that the molar mass ratio of core material powder: coating layer intermediate powder: lithium oxide is 1:0.3:0.9, and the rest is the same as Example 4.
[0064] Comparative Example 4
[0065] The difference from Example 4 is that the molar mass ratio of core material powder: coating layer intermediate powder: lithium oxide is 0.8:0.2:0.9, and the rest is the same as Example 4.
[0066] As shown in Table 1, Table 1 is a numerical table of the composition, density and ionic conductivity of the solid electrolyte sheets of Examples 1-6.
[0067] Table 1
[0068]
[0069] It can be seen from Table 1 that the lithium garnet solid electrolyte prepared by the method of the present invention has high density and high electrical conductivity.
[0070] As shown in Table 2, Table 2 is a numerical table of the density and ionic conductivity of the solid electrolyte obtained in Comparative Examples 1-4.
[0071] Table 2
[0072] Group Density% Ionic conductivity S / cm Solid electrolyte obtained in Comparative Example 1 95 <![CDATA[7.86×10 -5 ]]> Solid electrolyte obtained in Comparative Example 2 97 <![CDATA[1.32×10 -4 ]]> Solid electrolyte obtained in Comparative Example 3 98 <![CDATA[4.68×10 -4 ]]> Solid electrolyte obtained in Comparative Example 4 96 <![CDATA[9.02×10 -5 ]]>
[0073] As can be seen from Table 2, the molar ratio of the core material powder, the coating layer intermediate powder, and lithium oxide has a great influence on the density and ionic conductivity of the solid electrolyte. The present invention needs to strictly control their molar ratio to prepare a lithium garnet-type solid electrolyte with high density and ionic conductivity.
[0074] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for synthesizing a lithium garnet-type solid electrolyte, characterized in that: The following steps are included S1. Preparing precursor powder by coprecipitation method: heating and stirring the metal ion solution, adding alkaline solution to adjust the pH value of the solution to 9-12, keeping the pH value stable, aging the solution, filtering to obtain precursor residue, and drying the residue to obtain precursor powder; S2. Preparation of core material: lithium source, lanthanum source, precursor powder and doped metal oxide are taken as core raw materials according to the chemical composition ratio, the raw materials are mixed and ball milled, the ball milled material is dried and calcined to obtain core material powder; S3. Preparation of coating layer intermediate: taking lanthanum source, precursor powder and doped metal oxide as coating layer intermediate raw materials according to the chemical composition ratio, ball milling each raw material, drying and calcining the ball milled material to obtain coating layer intermediate powder; S4, tableting: core material powder, coating layer intermediate powder and lithium oxide are mixed and ball-milled, the ball-milled material is dried, the ball-milled material is sieved, and the sieved powder is tableted to obtain a formed sheet; S5. Sintering of the formed sheet: Covering the formed sheet with the core material powder and then sintering it, taking out the sheet and grinding and polishing it to obtain a lithium garnet type solid electrolyte.
2. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In S1, the preparation method of the metal ion solution is: weighing and mixing a lanthanum source and a zirconium source in a weight ratio of 1:1, adding an acidic solution or deionized water to dissolve the lanthanum source and the zirconium source, and obtaining a metal ion solution with a metal ion concentration of 100-200 g / L.
3. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 2, characterized in that: The acid concentration of the acidic solution is 0.1-1.5 mol / L, and the alkali concentration of the alkaline solution is 2-6 mol / L; the acid in the acidic solution is one or more of sulfuric acid, nitric acid, and hydrochloric acid; the alkali in the alkaline solution is one or more of ammonia water, ammonium carbonate, and ammonium bicarbonate.
4. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 2, characterized in that: The lanthanum source is one or more of lanthanum oxide, lanthanum carbonate, lanthanum hydroxide and lanthanum nitrate; the zirconium source is one or more of zirconium oxide, zirconium carbonate, zirconium hydroxide and zirconium nitrate.
5. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In S1, the heating temperature of the metal ion solution is 50-70° C., and the stirring speed is 300-600 rpm / min.
6. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In S2, the chemical composition of the core material powder is Li 7-nα-β M α Ln3Z 2-x M' x O 12 , wherein 0<α<1, 0≤x≤1, β=(n'-4)x, n is the valence state of element M, n' is the valence state of element M', M is at least one of B, Ca, Al, Y, Sc, Fe, and Ga, and M' is at least one of Ti, Mn, Bi, Sn, Ge, Mo, W, Sb, Nb, and Ta; and the metal doped with the metal oxide is one or more of metal M or M'.
7. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In S3, the chemical composition of the coating intermediate powder is La3Zr 2-x K x O 12 , wherein 0≤x≤1, K is one or more of Ti, Mn, Bi, Sn, Ge, Mo, W, Sb, Nb, and Ta; and the lanthanum source is lanthanum oxide.
8. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In S4, the molar mass ratio of the core material powder, the coating layer intermediate powder and the lithium oxide is 1:0.2:(0.7-1.1).
9. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In the S2, the calcination is carried out in an atmosphere with an oxygen content of 22%-99% and a temperature of 800°C-950°C for 5-10 hours; in the S3, the calcination is carried out in an atmosphere with an oxygen content of 22%-99% and a temperature of 700°C-850°C for 5-10 hours; in the S5, the sintering is carried out in an atmosphere with an oxygen content of 22%-99% and a temperature of 1100°C-1200°C for 5-15 hours.
10. The method for synthesizing a lithium garnet-type solid electrolyte according to claim 1, characterized in that: In S1, the solution is aged for 10-40 hours.
Citation Information
Cited By
Li-Zr double-site co-doped garnet solid electrolyte ceramic as well as preparation method and application thereof
CN120774711A